The Association Between Ascorbate and the Hypoxia-Inducible Factors in Human Renal Cell Carcinoma Requires a Functional Von Hippel-Lindau Protein - Wohlrab, Christina; Vissers, Margreet C. M.; Phillips, Elisabeth; Morrin, Helen; Robinson, Bridget A.; Dachs, Gabi U. (Frontiers in Oncology, 2018)
Hypoxia-inducible transcription factors (HIFs) drive angiogenesis and cancer cell growth, contributing to an aggressive tumor phenotype. HIF-α protein levels and activity are controlled at the post-translational level by HIF hydroxylases. Hydroxylated HIF-α is recognized by the von Hippel Lindau (VHL) tumor suppressor and targeted for degradation. The HIF hydroxylases are members of the iron and 2-oxoglutarate-dependent dioxygenases, which require ascorbate as cofactor for activity. Clear cell renal carcinomas (ccRCC) harbor mutations in the VHL gene, whereas papillary RCC (pRCC) have a functional VHL. These natural occurring VHL variants in RCC enable the testing, in clinical samples, of the hypothesis that ascorbate modulates HIF-α levels through its role as a cofactor for the HIF hydroxylases. We measured ascorbate, HIF-1α and HIF-2α protein and HIF downstream targets BNIP3, CA9, cyclin D1, GLUT1 and VEGF (combined to generate the HIF pathway score) in VHL-defective ccRCC (n = 73) and VHL-proficient pRCC human tumor tissue (n = 41). HIF and ascorbate levels were increased in ccRCC and pRCC tumors compared to matched renal cortex. HIF-1 and total HIF pathway activation scores were decreased with higher ascorbate in pRCC tumors (Spearman r = -0.38, p < 0.05 and r = -0.35, p < 0.05). This was not evident for ccRCC tumors. In mechanistic studies in vitro, ascorbate influenced HIF-1 activity in VHL-proficient, but not VHL-defective ccRCC cells. Our results indicate that ccRCC, which lacks a functional VHL, does not respond to ascorbate-mediated modulation of the HIF response. This contrasts with the demonstrated association between ascorbate content and the HIF pathway observed in pRCC and other tumors with a functional VHL. The results support a role for ascorbate as a modulator of HIF activity and tumor aggression in cancer types with a functional hypoxic response.